KONSEP PENDIDIKAN KARAKTER RELIGIUS KI HADJAR DEWANTARA - Solehah, Siti; Arnadi , Arnadi; Irawan , Deni (ILJ: Islamic Learning Journal, 2024)
This research aims to analyse the purpose of character education according to Ki Hadjar Dewantara and its relevance to current education. The research uses library research. library research. As for the techniques in This data collection technique uses  Data analysis technique with content analysis. The purpose of Ki Hadjar Dewantara's character education is independence, freedom physically and mentally without the existence of a religion. The purpose of Ki Hadjar Dewantara's character education is independence, namely freedom physically and mentally without coercion. coercion. So as to become a human being so that it becomes a whole human being with good character. While the concept education which concerns the principles of nationality, the principles of culture, the principles, the principles of independence, the principles of humanity, the principles of natural nature. humanity, the principle of natural nature. The foundation is tawakal and manunggaling kawula gusti. In the implementation of education, Ki Hadjar Dewantara uses the "Among" system, which consists of three pamong guidelines Ing Ngarso Sung Tuladha, Ing Madya Mangun Karsa, Tut Wuri Handayani. Handayani. besides that, the principle of educating using the method of asah, asih and foster. Using four stages of character education, namely shari'at, hakikat, tarikat and makrifat.and the implementation of the four stages and the implementation of the four stages using ngerti, ngrasa and nglakoni. In addition, Ki Hadjar Dewantara put forward three foundations of character education, namely the theory of continuity, continuity, and continuity. theory, namely the basis of continuity, concentricity, and convergence.